1980
DOI: 10.1021/bi00542a027
|View full text |Cite
|
Sign up to set email alerts
|

Conformational stability of ribosomal protein L7/L12: effects of pH, temperature, and guanidinium chloride

Abstract: The effects of pH, temperature, and guanidinium chloride on the conformation of ribosomal protein L7/L12 have been investigated in order to understand the stability of this protein dimer. The results indicate that many of the molecular forces stabilizing the conformation of the dimer are disrupted at low pH or high temperature. These acid- and thermal-denatured states, however, still retain considerable secondary structure. Approximately half of the alpha-helical content present in the native protein remains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The L7/ L12 ribosomal protein exists as a dimer in their biologically functional form, the monomers of which are identical except for the acetylated N-terminal serine of L7. The C-terminal fragment used in this study (termed Ctf) is, however, known to be remarkably stable in the isolated form as well (37) and thus suitable as a model protein.…”
Section: Methodsmentioning
confidence: 99%
“…The L7/ L12 ribosomal protein exists as a dimer in their biologically functional form, the monomers of which are identical except for the acetylated N-terminal serine of L7. The C-terminal fragment used in this study (termed Ctf) is, however, known to be remarkably stable in the isolated form as well (37) and thus suitable as a model protein.…”
Section: Methodsmentioning
confidence: 99%
“…The relative positions of the subunits in the dimer are unknown. While Gudkov et al (14) concluded that they were arranged in an antiparallel fashion, more convincing evidence (19,20) appears to suggest that they are parallel to each.other, i.e. the two amino terminii are located at one end and the carboxy terminii at the other end.…”
Section: Dimer Formationmentioning
confidence: 99%
“…This prediction was corroborated by circular dichroic studies which showed that the c~-helical content of either L7 or L12 ranged between 45-60% (11, 2 !, 22), and that it could be increased to 75-80% in the presence of a helix promoting solvent (22). A higher value of about 76% has recently been suggested based on a more complete analysis of the circular dichroic spectrum (20). Gudkov et al (23) have determined the helicity of various fragments of L7.…”
Section: Physical Characteristicsmentioning
confidence: 99%
“…Figure 1 shows the structure and principle of the ICkit. The ICkit targets the ribosomal protein L7/L12 antigen, which is a component of the 50S ribosome and contains an amino acid sequence speci c to each bacterial species [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…ICkit targets the ribosomal protein L7/L12 antigen, which is a component of the 50S ribosome and contains an amino acid sequence speci c to each bacterial species [20][21][22][23]. Sano et al and Ito et al reported the ICkit's utility in detecting the ribosomal protein L7/L12 in diagnosing Mycoplasma pneumonia and Legionella pneumonia [24,25].…”
Section: Introductionmentioning
confidence: 99%